Pengaruh Susu PDK terhadap Kenaikan Berat dan Tinggi Badan Anak Stunting dengan Gizi Kurang - Mutiara Nova Pratiwi (Jurnal Syntax Admiration, 2025)
Stunting is a child less than 5 years old who has a weight and height less than their age or more than minus 2 standard deviations from the WHO growth and development curve. The problem of stunting has long-term effects related to impaired cognitive function and academic achievement. This long-term effect can cause stunted children to experience motor and cognitive problems, thereby disrupting their physical and neurocognitive capacity. The growth and development of children under 5 years is influenced by macro and micro nutrition. Micronutrient deficiencies such as vitamin A, zinc, vitamin D and Fe are one of the important causes of stunting. These micro and macronutrients can be found in standardized formula milk. The aim of this research is to combine changes in weight and height in stunted children with malnutrition given formula milk for 3 months. This research method is experimental using the paired T test. The result is a P value <0.5, which means that there is a significant effect of giving PDK milk on weight and height gain in children aged 1-5 years with stunting and malnutrition.